(untitled) (Modern Problems of Metallurgy, 2025)
The problem of determining the temperatures of critical points of phase transformations in steels remains relevant due to the need to ensure high accuracy in assigning heat treatment modes. It is known that the position of critical points is largely determined by the chemical composition of the steel, in particular the content of alloying elements. The aim of the work is to determine, from among the known mathematical models, the most suitable ones for predicting the temperatures of critical points of multicomponent economically alloyed structural steels. The research was conducted by comparative analysis of the results of calculations using known mathematical models used to determine the temperatures of critical points of phase transformations in multicomponent economically alloyed structural steels, and experimental data for the studied steels and the prototype steel. The chemical composition of the studied steels was determined on a precision analyzer EXPERT 4L. The studied steels were smelted from charge materials of technical purity in an induction module ІТПЕ-0,01. The melting was carried out by the remelting method without forced oxidation of impurities. The introduction of alloying elements into the liquid steel was carried out by immersing a protective metal container into it, where samples of the necessary alloying elements were placed. To identify structural and phase transformations of the prototype steel, the method of differential thermogravimetric analysis was used, which was carried out on a synchronous thermal analyzer STA 449 C Jupiter. The results of a comparative analysis of mathematical models used to predict the temperatures of critical points of phase transformations in multicomponent economically alloyed structural steels are presented. The influence of alloying elements on the values of critical temperatures is analyzed, and the conditions for the application of various mathematical models are also considered. It was found that the studied mathematical models allow to establish the values of critical points of steels with relatively low accuracy. Nevertheless, based on the fact that in practice, the most significant temperature for setting the tempering temperature is the Ac3 temperature, and the real tempering temperature, from a technological point of view and the equipment used for heat treatment, may exceed the Ac3 point temperature by 30…100 °C, it is recommended to calculate the Ac3 temperature value for economically alloyed structural steels with a sufficiently high level of accuracy using mathematical models of the Jmat PRO or ISI software complex..